Corruption and its diverse effect on credit risk: Global evidence - Rashedul Hasan; Muhammad Ashfaq (Future Business Journal, 2021)
Corruption has a complex relationship with economic growth. We have explored the impact of corruption on credit risk from a global perspective. The sample consists of 178 countries and covers 18~years that range from 2000 to 2017. Non-performing loan (NPL) is used as a proxy for credit risk and data regarding NPL is collected from the World Bank Database. Corruption scores are collected from the Transparency International reports. Panel regression results provide a positive association between corruption and credit risk for the global sample. Generalized Methods of Moments regression and robustness tests validate the findings. However, sub-sample analysis provides support for "grease the wheel" hypothesis for high corruption countries and indicates that corruption is beneficial in a weak form of governance and excessive regulatory pressure. This study advocate for the importance of strong governance mechanisms in high corruption countries that can minimize the impact of corruption on banking sector profitability and ensure economic development. Unlike past literature, we provide global evidence on the association between corruption and credit risk for the banking sector which allows generalizability.
Keywords: D73; G21; 650; Banks; Bureaucracy; Corporate finance and governance; Corruption; Credit risk